A Miocene impact ejecta layer in the pelagic Pacific Ocean - Nozaki, Tatsuo (Sci Rep, 2019)
Meteorite impacts have caused catastrophic perturbations to the global environment and mass extinctions throughout the Earth’s history. Here, we present petrographic and geochemical evidence of a possible impact ejecta layer, dating from about 11 Ma, in deep-sea clayey sediment in the Northwest Pacific. This clay layer has high platinum group element (PGE) concentrations and features a conspicuous negative Os isotope anomaly ((187)Os/(188)Os as low as ~0.2), indicating an influx of extraterrestrial material. It also contains abundant spherules that include pseudomorphs suggestive of porphyritic olivine as well as spinel grains with euhedral, dendritic and spherical forms and NiO contents as great as 23.3 wt%, consistent with impact ejecta. Osmium isotope stratigraphy suggests a most plausible depositional age of ~11 Ma (Miocene) for this layer, as determined by fitting with the seawater evolution curve. No large impact crater of this age is known on land, even within the relatively large uncertainty range of the relative Os age. Thus, we suggest that an unrecognised impact event in the middle or late Miocene produced the impact ejecta layer of the Northwest Pacific.